Изучение макро- и микроэлементного состава волос у школьников г. Минска - Зайцев, В.А.; Плешкова, А.А.; Бутько, З.Т.; Гузик, Е.О.; Гресь, Н.А. (Актуальні проблеми транспортної медицини, 2014)
Проведены исследования минерального состава волос школьников г. Минска, которые позволяют определить региональные особенности обеспеченности химическими элементами организма детей для общей оценки состояния их здоровья. Проведено дослідження мінерального складу волосся школярів м. Мінська, які дозволяють визначити регіональні особливості забезпеченості хімічними елементами організму дітей для загальної оцінки стану їх здоров’я. Studies of mineral composition of hair of schoolchildren are undertaken Minsk. It is set that for the city of Minsk a problem of high-purity of deficits is actual for the schoolchildren of calcium, magnesium and zinc. The study of macro- and microelement imbalance in school-age children in Minsk Belarus is the scientific rationale for the development of a regional program of creating health-environment in terms of overcoming the lack of macro- and micronutrients and improve the efficiency of the prevention of functional disorders and diseases of Belarusian students in institutions of secondary conditions education.